KOSAKATA DAN IDEOLOGI BAHASA PEREMPUAN DALAM NOVEL Ã¢Â€ÂœTANAH TABUÃ¢Â€Â KARYA ANINDITA S. THAYF - Baru, Yosefina (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2018)
The language of women can be addressed as a discourse, which is a way to express the events, experiences, views, and reality of a womanÃ¢Â€Â™s life. The language of women describes the model of a particular view of life, which is a description of the idea of life and life that has been interpreted and processed by women. While vocabulary is all words contained in a language, related to this topic are all words produced by womenÃ¢Â€Â™s ideas, experiences, about his world. There are three values possessed by formal linguistics, namely experience value, relational value, and expressive value. While the language ideology is primarily seen in the production of texts produced by a woman because the female language ideology can bea sign and expression of the contents of a sign expressed through context or text. Values and ideologies can be described through vocabulary through the conversation of characters in the novel Ã¢Â€ÂœTanah TabuÃ¢Â€Â by Anindita S. Thayf.